Resistance of melon cultivars to Bemisia tabaci biotype B - Baldin,Edson LL (2012)
The silverleaf whitefly, Bemisia tabaci biotype B, is currently one of the most important pests of melon, causing direct and indirect damage to plants, and significantly reducing production in the field. Due to the need for alternative methods of chemical control in melon crops, the melon cultivars AF-646, AF-682, Don Luis, Frevo, Jangada, Nilo, Vereda, Amarelo Ouro and Hales Best were assessed at field, greenhouse, and laboratory trials for resistance to whitefly B. tabaci biotype B. In general, 'Hales Best' and 'Amarelo Ouro' were the most resistant, showing oviposition non-preference against whitefly. The trichome density is associated with the variation in oviposition on the cultivars and should be further investigated in future work. These results may be helpful in melon breeding programs, focusing on plant resistance to B. tabaci biotype B.